2017
DOI: 10.1021/acs.analchem.6b04944
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Nonaqueous Capillary Electrophoresis–Mass Spectrometry Method for Determining Active Ingredients in Plant Extracts

Abstract: Nonaqueous capillary electrophoresis (NACE) is very well suited for online coupling with mass spectrometry due to the relatively high volatility and low surface tension of most organic solvents. Here we present a quantitative NACE-ESI-MS/MS method for separating and determining physcion, chrysophanol, and aloe-emodin in rhubarb. Dantron was used as an internal standard to ensure accuracy and reproducibility in quantitative analyses. Parameters including the pH, background electrolyte (BGE) composition, flow-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Metabolic profiling was performed on rodent muscle , heart , liver , brain , intestinal and glioma tissue, arterial cells as well as on rodent serum/plasma , urine and feces . CE‐MS was furthermore used for research on the metabolism of microorganism , plants and mushroom . Additional publications are included in Table .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Metabolic profiling was performed on rodent muscle , heart , liver , brain , intestinal and glioma tissue, arterial cells as well as on rodent serum/plasma , urine and feces . CE‐MS was furthermore used for research on the metabolism of microorganism , plants and mushroom . Additional publications are included in Table .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Capillary electrophoresis (CE) offers an orthogonal separation platform for FA analysis that is applicable to volume-restricted samples when using detergents or organic solvents in the background electrolyte (BGE) in conjunction with direct or indirect UV absorbance, capacitively coupled contactless conductivity, or fluorescence detection . Yet, there have been few reported studies for FA determination when using nonaqueous-CE when coupled to electrospray ionization-MS (NACE-MS) , with most methods applied to analyze water-insoluble pharmaceuticals, peptides, or natural products. Recently, Lee et al reported the use of a dicationic ion pair reagent added to the sheath liquid to form a dynamic complex with saturated FAs during ion desorption to improve their ionization responses under positive ion mode conditions. However, this method was not extensively validated and longer chain FAs (>C16) were prone to deleterious band broadening due to insufficient acetonitrile content in the BGE with modest enhancements to concentration sensitivity .…”
mentioning
confidence: 99%
“…Although UV had been the most frequently used detection method in CE, MS was also widely used due to the high sensitivity and selectivity. Few examples are determination of mushroom toxins ibotenic acid, muscimol and muscarine in human urine , fingerprinting analysis of flavonoids in Ginkgo biloba herbal supplements , and fast determination of harmala alkaloids in edible algae by CE‐MS; Differential detection of Rhizoma coptidis by CE‐MS with a nanospray interface ; Characterization of hydrothermally isolated xylan from beech wood by CE‐laser‐induced fluorescence (LIF) and MS detection ; Analysis of paspalic acid, lysergic acid, and iso‐lysergic acid with UV and Q‐TOF/MS detection ; Dereplication of known nucleobase and nucleoside compounds in natural product extracts by CE‐high resolution mass spectrometry (HR‐MS) ; Separating and determining physcion, chrysophanol and aloe‐emodin in rhubarb and quantifying palmatin, columbin, cepharanthine, menisperine, magnoflorine and 20‐hydroxyecdysone in Radix tinosporae by NACE‐MS.…”
Section: Methods Developmentmentioning
confidence: 99%